The problem is
2 + (1 / y + 1) - (1 / y - 1) = 0
Ok what I did was Mulitply the entire equation by the common denominator of
(y + 1)(y - 1).
I end up getting
2(y + 1)(y - 1) + y - 1 - y + 1 = 0
From here, I keep working the problem until it gets to
2(y^2 - 1) = 0
2y^2 - 2 = 0
(2y^2 - 2) / 2
y^2 - 1 = 0
y^2 = 1
Square root both sides to get
y = +- 1
The problem is, when entering either one of these solutions into the original problem, i'm always getting one of the divisions within the problem where the denominator is 0 and that is undefined....so i'm kinda lost. Is there no solution or?